Early prediction of twin‐to‐twin transfusion syndrome: systematic review and meta‐analysis. (May 2017) - Stagnati, V.; Zanardini, C.; Fichera, A.; Pagani, G.; Quintero, R. A.; Bellocco, R.; Prefumo, F.
Abstract: Objective: To assess the role of first‐ and early second‐trimester markers in the prediction of twin‐to‐twin transfusion syndrome (TTTS) in monochorionic twin pregnancies. Methods: Electronic databases MEDLINE, EMBASE andClinicalTrials.gov were searched from inception to April 2014, using the MeSH term 'fetofetal transfusion' in combination with phrases 'predictive value', 'sensitivity', 'specificity', 'false positive', 'false negative', 'screening', 'accuracy' and 'ROC'. Study quality was assessed using the PRISMA guidelines and QUADAS‐2 tool. A meta‐analysis was planned for the following predictive factors: intertwin nuchal translucency (NT) discrepancy; NT > 95 th percentile in at least one twin; intertwin crown–rump length (CRL) discrepancy as a percentage of the larger CRL; abnormal ductus venosus (DV) flow in at least one twin. The outcome assessed was TTTS, defined according to the presence of a twin oligohydramnios–polyhydramnios sequence. The diagnostic performance of the predictive factors was evaluated for each included study. Results: The electronic search identified 152 records, of which 23 were assessed in full for eligibility. We identified 13 eligible studies that reported the predictive accuracy of ultrasound parameters, measured before 16 weeks, for the development of TTTS, including a total of 1991 pregnancies, of which 323 developed TTTS. An increased risk of TTTS was associated with: intertwin NT discrepancy (positive likelihood ratio (LR+), 1.92 (95% CI, 1.25–2.96); negative likelihood ratio (LR–), 0.65 (95% CI, 0.50–0.84)); NT > 95 th percentile (LR+, 2.63 (95% CI, 1.51–4.58); LR–, 0.85 (95% CI, 0.75–0.96)); CRL discrepancy > 10% (LR+, 1.80 (95% CI, 1.05–3.07); LR–, 0.92 (95% CI, 0.81–1.05)); abnormal DV flow (LR+, 4.77 (95% CI, 1.33–17.04; LR–, 0.49 (95% CI, 0.17–1.41)). The highest sensitivities were observed for intertwin NT discrepancy (52.8% (95% CI, 43.8–61.7%)) and abnormal DV flow (50.0% (95% CI, 33.4–66.6%)). Conclusion: Monochorionic twin pregnancies with intertwin NT discrepancy, NT > 95 th percentile, intertwin CRL discrepancy > 10% or abnormal DV flow on first‐trimester ultrasound examination are at significantly increased risk of developing TTTS. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.